PRAKTIK KONSUMSI SELEBRITI DALAM KOMUNITAS PENGGEMAR DI ERA MEDIA BARU (Studi Kasus Komunitas Penggemar NIC Jogja dan Jakarta) - Lidwina Mutia Sadasri (Profetik: Jurnal Komunikasi, 2017)
Celebrity as a media person is not a new thing on the context of communication studies. On some various contexts, celebrities are benefited with its added value on popularity. The construction of value that been built by celebrities are also studied, particularly in relation with new media development, through the dynamic of information and communication technology. On the context of celebrity’s consumption on the perspective of cultural function on new media, one of the concepts that appear is celebrity watchers. Consumption type also varied and it needs depth identification on academic studies, one of them is consumption practice that manifested on fandom. Fan typology inside the fandom also been analysed to see the meaning that been interpreted by audiences of the celebrity’s message. By using case study on the context of Agnez Monica’s fanbase (Nez In da Club or NIC), we found out that on the context of NIC Jogja and Jakarta, there are various type of fans, such as enthusiast, cultist, and petty producer.